Whither Participation? Evaluating Participatory Policy Processes Using the CGPE Approach: The Case of CAADP in Malawi - Henning, Christian; Hedtrick, Johannes; Séne, Ligane Massamba; Krampe, Eva (Springer, 2018)
In this chapter, we apply the CGPE model to analyzing the performance of policy processes with respect to the production of efficient policy choices. Within the CGPE approach participation of stakeholder organizations is modeled in two ways. First, as classical lobbying influence and second as informational influence within a model of political belief formation. An empirical application of the CGPE model to CAADP reforms in Malawi delivered the following results: (i) inefficient agricultural policies mainly result from lack of adequate political knowledge, while biased political incentives play only a minor rule. (ii) Policy beliefs of political practitioners differ significantly from economic models. Hence, our analyses imply a cleavage between the world of economic modeling and the world of political practice. (iii) As Bayesian estimation combining objective knowledge of scientific models with the subjective wisdom of practitioners results in a compromise of both worlds, we conclude that adequate political knowledge does not yet exist in the scientific system or in political praxis and must be created in the political process. (iv) Therefore, the only effective political therapy corresponds to the application of adequate tools that facilitate interactive communication and policy learning among stakeholders and economic modelers.